Expanding the Clinical and Immunological Phenotypes and Natural History of MALT1 Deficiency - ÖZEN, AHMET OĞUZHAN; KOLUKISA, BURCU; AYDINER, ELİF; BARIŞ, SAFA (SPRINGER/PLENUM PUBLISHERS, 2022)
Purpose MALT1 deficiency is a combined immune deficiency characterized by recurrent infections, eczema, chronic diarrhea, and failure to thrive. Clinical and immunological characterizations of the disease have not been previously reported in large cohorts. We sought to determine the clinical, immunological, genetic features, and the natural history of MALT-1 deficiency. Methods The clinical findings and treatment outcomes were evaluated in nine new MALT1-deficient patients. Peripheral lymphocyte subset analyses, cytokine secretion, and proliferation assays were performed. We also analyzed ten previously reported patients to comprehensively evaluate genotype/phenotype correlation. Results The mean age of patients and disease onset were 33 +/- 17 and 1.6 +/- 0.7 months, respectively. The main clinical findings of the disease were recurrent infections (100%), skin involvement (100%), failure to thrive (100%), oral lesions (67%), chronic diarrhea (56%), and autoimmunity (44%). Eosinophilia and high IgE were observed in six (67%) and two (22%) patients, respectively. The majority of patients had normal T and NK cells, while eight (89%) exhibited reduced B cells. Immunoglobulin replacement and antibiotics prophylaxis were mostly ineffective in reducing the frequency of infections and other complications. One patient received hematopoietic stem cell transplantation (HSCT) and five patients died as a complication of life-threatening infections. Analyzing this cohort with reported patients revealed overall survival in 58% (11/19), which was higher in patients who underwent HSCT (P = 0.03). Conclusion This cohort provides the largest analysis for clinical and immunological features of MALT1 deficiency. HSCT should be offered as a curative therapeutic option for all patients at the early stage of life.
Keywords: Inborn errors of immunity; primary immunodeficiency; MALT1; combined immune deficiency; immune dysregulation; recurrent infections; skin involvement; failure to thrive; hematopoietic stem cell transplantation; NF-KAPPA-B; T-CELL; COMBINED IMMUNODEFICIENCY; MUTATIONS; ACTIVATION; CARMA1; ROLES